Alfalfa water use under deficit irrigation for farm savings - Sitterson, Jan, author; Andales, Allan A., advisor; Mooney, Daniel F., committee member; Brummer, Joe E., committee member (Colorado State University. Libraries, 2022)
Colorado water law allows for water rights to be leased between agriculture and municipality users. Decreasing the consumptive use (CU) of agricultural land while maintaining profits and yields will allow farmers to lease their water rights for revenue. Deficit irrigation is a water-saving approach to avoid the complete dry up of irrigated farmland while providing profitable yields and monetary gains from water transfers. To maximize water savings, efficient irrigation systems such as subsurface drip irrigation (SDI) are used to prevent water losses from soil evaporation. This study evaluated the feasibility of using SDI with deficit irrigation practices to grow alfalfa (Medicago Sativa L.) at production scale in northeast Colorado (2018 – 2022). Alfalfa was found to have good potential for decreasing CU due to its drought tolerance, multiple harvests per season, and improved quality of hay with less irrigation water. The Water Irrigation Scheduler for Efficient Application (WISE) model was also found to be a useful tool for estimating CU of deficit irrigated alfalfa and the regrowth phases after multiple harvests in a growing season. Mid-season corrections of the soil water deficit in WISE improved the accuracy of modeled CU. Overall the water savings from deficit irrigation at low, medium, and high irrigation levels with an SDI system can be profitable when prices for leasing water exceed hay prices per unit area of production.
Keywords: crop modeling; subsurface drip irrigation; deficit irrigaion; alfalfa